2023
DOI: 10.1186/s40494-023-00881-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected solvents on PMMA after prolonged exposure: unilateral NMR and ATR-FTIR investigations

Abstract: Exposure of heritage plastics to solvents can cause several changes to their surface layers and bulk. The amorphous nature of certain plastics, particularly polymethyl methacrylate (PMMA), allows penetration and diffusion of low-molecular liquids, which can lead to swelling, cracking, plasticisation or stiffening, extraction and dissolution of polymer and additive components. Such phenomena compromise the visual characteristics, chemical and physical structure of heritage collections and remain, for the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Conversely, the present study found that alcohol-free agents could better preserve the original mechanical properties or even enhance the Vickers hardness. A previous study showed that even when the polymer was immersed in water for a long period of up for 30 days, although water continued to be absorbed throughout the immersion period, neither relaxation behavior nor plastic deformation could be detected 26 . Although both alcohol and water are known to be absorbed by polymer networks, alcohols would weaken the mechanical properties of the contacted polymer and act more aggressively 31 , potentially even causing visible cracks on the polymer surface 26 .…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Conversely, the present study found that alcohol-free agents could better preserve the original mechanical properties or even enhance the Vickers hardness. A previous study showed that even when the polymer was immersed in water for a long period of up for 30 days, although water continued to be absorbed throughout the immersion period, neither relaxation behavior nor plastic deformation could be detected 26 . Although both alcohol and water are known to be absorbed by polymer networks, alcohols would weaken the mechanical properties of the contacted polymer and act more aggressively 31 , potentially even causing visible cracks on the polymer surface 26 .…”
Section: Discussionmentioning
confidence: 94%
“…A previous study showed that even when the polymer was immersed in water for a long period of up for 30 days, although water continued to be absorbed throughout the immersion period, neither relaxation behavior nor plastic deformation could be detected 26 . Although both alcohol and water are known to be absorbed by polymer networks, alcohols would weaken the mechanical properties of the contacted polymer and act more aggressively 31 , potentially even causing visible cracks on the polymer surface 26 . This may explain why the mechanical properties of the samples washed with water were more stable and superior than those washed in alcohol.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The solvent choice, its interaction with polyurethane, and its effectiveness in removing uncured resin and impurities are crucial factors, as stated by Gomez et al [ 32 ]. Ethanol, a less aggressive solvent compared to isopropanol, has shown promise in preserving the material’s integrity during the post-processing of PMMA materials [ 33 ]. When combined with an inert nitrogen polymerization environment, it contributes to higher conversion rates, potentially enhancing the aligner’s performance [ 34 ].…”
Section: Introductionmentioning
confidence: 99%